A Conversation with Justice Ruth Bader Ginsburg - Ginsburg, Ruth Bader; Metzger, Gillian; Gluck, Abbe (Columbia Journal of Gender and Law, 2013)
Professor Gillian Metzger: Katherine, thank you for that wonderful overview of all that the Justice has achieved and the history of Columbia Law School. And I want to apologize for those to whom I am showing my back, but this will allow us to have more of a conversation with the Justice. Justice, thank you so much for being with us today. It is a real privilege for us to get to talk to you this way, and we know for the entire audience. You have had-as you have now heard (LAUGHS)-an amazing and just tremendously varied career, spanning so many different roles of academic, public interest advocate, judge, now Justice. We can’t possibly cover all of this in the time we have this morning, but what we are hoping to do is talk a little bit about each of these roles, how each step you took influenced the rest, and then we will be throwing it open after our conversation for questions from the audience.